Long-Term Outcomes of Acute Osteoarticular Infections in Children - Manz, Nora; Krieg, Andreas H.; Buettcher, Michael; Ritz, Nicole; Heininger, Ulrich (Frontiers in Pediatrics, 2020)
Background: Acute hematogenous osteomyelitis (OM) and septic arthritis require immediate diagnosis and treatment by an interdisciplinary team of pediatric infectious disease specialists and pediatric orthopedic surgeons. Adverse outcomes such as growth disturbance, bone deformity, and chronic infections have been described in older studies. However, there is only little known about long-term follow-up of patients of the last two decades. Therefore, we aimed to evaluate subjective and objective long-term outcomes of these children with osteoarticular infections treated in the millennial years. Methods: Cross-sectional study performed in two pediatric centers including patients admitted for OM and/or SA between 2005 and 2014 and follow-up consultations in 2019. Patients with symptoms of ≤2 weeks duration at initial presentation were contacted. Subjective outcomes were assessed by standardized interview, objective outcomes by clinical examination. Medical charts were used to extract data from the initial presentations. Statistical analysis was performed by non-parametric tests and Fisher's exact test. Results: Of 147 eligible patients 77 (52%) agreed to participate, of which 68 (88%) had an interview and physical examination and 9 (12%) an interview only. Thirty-three (39%) had OM, 26 (34%) SA, and 21 (27%) combined OM/SA. Median (IQR) age at follow-up was 13.3 (10.5–18.0) years with a median (IQR) follow-up of 7.1 (6.1–8.6) years. Persistent complaints including pain, functional differences and scar paresthesia, reported by 21 (28%) patients, were generally mild and only 3 (5%) required ongoing medical care. Objective sequelae including pain, limited range of motion, unilateral axis deformity or asymmetric gait were found in 8 (12%) participants. Older age, female sex, joint involvement, surgical intervention, persistent fever, and C-reactive protein elevation were associated with adverse clinical outcome. Conclusions: Adverse outcomes were observed in a considerable number of patients, most of which were minor, and only few required ongoing medical care. Long-term follow up is advisable for patients with risk factors identified during the initial presentation. This study was registered on ClinicalTrials.gov (NCT03827980).